Авторская стилевая концепция и ее отражение впереводе (Заметки о переводах тетралоrии Х. Лакснесса “Свет мира”) - Неделяева-Степонавичене, С. И. (Kalbotyra, 1981)
The tetralogy “World Light” presents for the translator greater difficulties than any other Laxness’ work because of the complexity and the deeply hidden character of the author’s stylistic conception. The stylistic peculiarities of the tetralogy are deeply rooted in the character of the scald Ólafur Kárason, who, in conformity with the author’s conception, embodies the poet “in puris naturalibus” and is at one and the same time both the leading character in the novel and also its author.